How mobile phone towers could help monitor rainfall in developing countries - David, Noam; Gao, H. Oliver; Liu, Yanyan (The Conversation, 2020)
Many developing economies suffer from a lack of reliable rainfall measurements due to a lack of funds and a shortage of equipment – such as gauges and radars. Even if countries are equipped with these monitoring instruments, they all have limitations.